The Role of Visual Imagery in Building Brand Image and Consumer Purchase Intention in the Era of Social Media: A Literature Review - Angga Dibda; Hafiz Aziz Ahmad (Transpublika Publisher, 2025)
Visual-based social media platforms such as Instagram have become a primary channel for brand communication in the digital marketing era, particularly among Gen Z and Millennials, both highly visual-oriented consumers. This study explores how visual imagery shapes brand image and purchase intention on social media, with a particular focus on these two generational segments. Using a narrative literature review approach, the article synthesizes insights from recent studies examining the relationships between visual imagery elements, brand perception, and consumer decision-making processes. The findings highlight the strategic role of visual imagery in fostering positive brand associations, enhancing brand personality, and eliciting emotional responses that directly influence purchase intention. Gen Z and Millennials’ preference for authentic, aesthetically pleasing, and emotionally resonant visual imagery emerges as a critical factor in the success of visual marketing strategies on social media. These insights contribute to the theoretical development of visual communication research and offer practical guidance for brands aiming to design more effective and relevant visual content on visual-first platforms such as Instagram.